Children First? Changing Attitudes Toward the Primacy of Children in Five European Countries. (December 2015) - Ivan, Georgiana; Da Roit, Barbara; Knijn, Trudie
Parenting support is a new policy field, directed toward teaching parents how to assume their role. Its foundations are embedded in a child-centered social investment approach, which is becoming dominant in Western European welfare states. This article aims at exploring the extent to which ideas underlying these policies are coherent with individual attitudes toward children, parents, their relationship and their change over time. We analyze how these attitudes changed in five selected countries (France, Germany, the Netherlands, the United Kingdom, and Sweden), using data from all four waves of the European Values Study (1981, 1990, 1999, 2008). We also test what kind of values are behind these attitudes, employing logistic regression as method. Our main finding is that there has been a value shift in public sentiments regarding the primacy of children, which is no longer to be viewed as a traditional type of attitude.